Bobby Flay's Grill It! - Flay, Bobby; Banyas, Stephanie; Jackson, Sally 1978- (New York : Clarkson Potter/Publishers, 2008)
Presents a guide to grilling that features more than 150 simple recipes, organized by ingredients, for a wide variety of meat, poultry, seafood, vegetable, fruit, and dessert dishes.
The grill -- The pantry -- Asparagus -- Beef -- Burgers -- Chicken -- Corn -- Fruit -- Lamb -- Lobster -- Mushrooms -- Pork -- Potatoes -- Salmon -- Scallops -- Shrimp -- Squash and eggplant -- Tuna -- White fish.
Includes index.
Keywords: Barbecue cooking